90.3k views
5 votes
4(x-3)= -3x + 23 show your work ​

User Xlogic
by
5.6k points

2 Answers

3 votes

Answer:

x=5

Explanation:

4 • (x - 3) - (23 - 3x) = 0

7x - 35 = 7 • (x - 5)

7 • (x - 5) = 0

7 = 0

x-5 = 0

x = 5

User CamomileCase
by
6.3k points
3 votes

Answer:

x = 5

Explanation:

Expand the brackets

4x - 12 = -3x + 23

Rearrange by collecting the like terms, so that the variables are on one side and the constants are on the other

4x + 3x = 23 + 12

7x = 35

Divide both sides by 7 to make variable on its own

x = 35/7

x = 5

User Zuzuleinen
by
6.0k points